Becoming the Other: Gender Reversals in Croatian Carnival and Wedding Customs - Škrbić Alempijević, Nevena (Array, 2004)
The ritual adoption of the "face" of the opposite sex is an act of crossing everyday boundaries, the construction of an upside-down world. The mask encompasses the multiplicity of gender identities, one of which is hidden and temporarily suppressed, while the other is symbolically constructed and overemphasised. The aim of this paper is to discuss, on the basis of data gathered through fieldwork and archival records, the means by which the image of the opposite sex is created in customs: masks, dress, mimicry, manner of walking, behaviour, performing of activities traditionally attributed to the opposite sex, etc. The moments within clearly defined frames of wedding and carnival rituals which allow for the appearance of such masks, as well as the criteria for deciding which members of a community can assume the role of the other sex will also be discussed. Finally, the meanings and functions of ritual gender reversal change along with shifts in the context in which they occur. The folk-customs stage presentation at the International Folklore Festival in Zagreb, in which cross-dressed performers took part, will serve as an example of the way in which masks themselves, as well as their roles, change